Ibn Khaldūn's Epistemology of Natural Science within his Philosophy of History: A Socio-Economic Analysis - Salsabila Dwi Putri; Imam Rasikh Islami; Putri Julianti; Lukmanul Hakim (Nur Science Institute, 2025)
Abstract Ibn Khaldun, a Muslim who lived in the 14th century and was known as a philosopher and historian, made important contributions to developing social and economic thought, particularly through his famous work, the Muqaddimah. In Ibn Khaldun's view, history is not merely seen as a series of isolated events but as a process influenced by social, economic, and natural factors. One of the main concepts he introduced was 'Natural Science,' which encompasses the study of physical and social factors that influence the development of society. This article explores how Ibn Khaldun viewed the relationship between 'Natural Science' and social and economic development in the context of the philosophy of history. Through an interdisciplinary approach, this concept reveals the idea of the cycle of progress and decline of civilizations influenced by the physical, social, and economic conditions of society. Keywords: Ibn Khaldun, Natural Science, Philosophy of History, Social, Economics Amin, Khairul. 2018.